2021
DOI: 10.1080/17425255.2021.1946514
|View full text |Cite
|
Sign up to set email alerts
|

GenotypingHLAalleles to predict the development of Severe cutaneous adverse drug reactions (SCARs): state-of-the-art

Abstract: Introduction: Pharmacogenomics has great potential in reducing drug-induced severe cutaneous adverse drug reactions (SCARs). Pharmacogenomic studies have revealed an association between HLA genes and SCARs including acute generalized exanthematous pustulosis (AGEP), drug reaction with eosinophilia and systemic symptoms (DRESS), Stevens-Johnson syndrome (SJS), and toxic epidermal necrolysis (TEN). Areas covered: Pharmacogenomics-guided therapy could prevent severe drug hypersensitivity reactions. The US Food an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 107 publications
0
12
0
Order By: Relevance
“…Cutaneous adverse drug reactions (cADRs) such as Stevens−Johnson syndrome (SJS), toxic epidermal necrolysis (TEN), maculopapular exanthema (MPE), and drug reaction with eosinophilia and systemic symptoms (DRESS) are life‐threatening hypersensitivity reactions affecting predominantly the mucous membranes and skin 1–3 . The incidence of cADRs is generally found to be low, but the mortality rates associated with cADRs are high enough (SJS ~1–5%, TEN ~25–35%, DRESS ~10%) to be clinically concerning as reported elsewhere 4 . Medication use (~80% of cases) is one of the most identified and widely accepted reasons for developing life‐threatening cADRs.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Cutaneous adverse drug reactions (cADRs) such as Stevens−Johnson syndrome (SJS), toxic epidermal necrolysis (TEN), maculopapular exanthema (MPE), and drug reaction with eosinophilia and systemic symptoms (DRESS) are life‐threatening hypersensitivity reactions affecting predominantly the mucous membranes and skin 1–3 . The incidence of cADRs is generally found to be low, but the mortality rates associated with cADRs are high enough (SJS ~1–5%, TEN ~25–35%, DRESS ~10%) to be clinically concerning as reported elsewhere 4 . Medication use (~80% of cases) is one of the most identified and widely accepted reasons for developing life‐threatening cADRs.…”
Section: Introductionmentioning
confidence: 94%
“… 1 , 2 , 3 The incidence of cADRs is generally found to be low, but the mortality rates associated with cADRs are high enough (SJS ~1–5%, TEN ~25–35%, DRESS ~10%) to be clinically concerning as reported elsewhere. 4 Medication use (~80% of cases) is one of the most identified and widely accepted reasons for developing life‐threatening cADRs. Although different medications such as allopurinol, phenytoin, abacavir, dapsone, flucloxacillin, and cotrimoxazole have been strongly associated with cADRs, carbamazepine (CBZ) is the most studied and causes SJS/TEN in a considerable proportion of patients.…”
Section: Introductionmentioning
confidence: 99%
“…The future of pharmacogenomics-guided therapy in clinical settings across Thailand appears promising because of the availability of evidence of clinical validity of the pharmacogenomics testing (Sukasem et al, 2021a). The effectiveness of HLA screening on a wider scale in clinical practice requires significant resources, including state-of-theart laboratory; multidisciplinary team approach, and healthcare provider education and engagement; clinical decision support alert system via electronic medical record (EMR); laboratory standards and quality assurance; evidence of cost-effectiveness; and cost of pharmacogenomic tests and reimbursement (Jantararoungtong et al, 2021a).…”
Section: Hlamentioning
confidence: 99%
“…Reasons for these observed regional variations are likely multifactorial, whether it be more robust electronic health record documentation ( 37 ), or genuine biological ethnic-specific differences. Historically, certain high-risk HLA alleles were identified to be associated with carbamazepine and allopurinol-induced drug allergy among Asian patients, but not BL or anti-microbials ( 38 , 39 ). Interestingly, a recent Thai study found HLA-B*48:01 to be associated with immediate-type reactions to BL, whereas HLA-C*04:06, HLA-C*08:01 and HLA-DRB1*04:06 were associated with delayed reactions ( 40 ).…”
Section: Epidemiology: East Vs Westmentioning
confidence: 99%